Exploring the Benefit and Sacrifice Factors of Virtual Reality Gameplay - Lee, Chun-Chia; Hsiao, Kuo-Lun; Chen, Chia-Chen (Frontiers in Psychology, 2020)
Although Virtual reality (VR) entertainment is now relatively popular, the adoption of VR devices is still low. In consumer intention studies, perceived value theory is widely adopted to explore the antecedents of purchase or adoption intention. This study adopted perceived value as a base model to provide insights into the factors contributing to players’ intention to use VR devices to play games. An online questionnaire was developed and distributed in a university in Taiwan and on popular websites to collect data. The responses of 152 inexperienced users and 150 experienced users were collected. The eleven hypotheses were validated by using partial least squares (PLS) techniques. According to the results of the analysis, the influences of the benefit factors (flow, spatial presence, and relaxation) on the adoption intention in two groups are consistent. All of the positive influences are supported. Moreover, visual fatigue had the strongest negative effects on flow and intention. Users with a high level of openness to experience are more possible to adopt VR devices. The findings can provide insights to VR device developers to design their VR devices/contents and marketing strategies.